Structural Analysis of the Oxymoron in the Sonnets of William Shakespeare - Sakaeva, Liliya R.; Kornilova, Liya A. (Journal of History Culture and Art Research, 2017)
This paper considers the structural groups of oxymoron in the Russian and English languages. It is also relevant to study oppositional lexical units represented in heterogeneous system languages from the standpoint of linguistic and extra linguistic meanings, since the figures of contrast are inconceivable without the associative-emotional and evaluative qualifications of the objects of opposition. They give the analysis of the oxymoron’s nature and its functions in two different-structured languages. The article has carried out lexical and semantic characteristics of oxymoron. In the linguistic literature there is no generalized, concrete and universal structural and semantic classification of this stylistic device. This study attempts to create a structural and semantic classification, combining all the existing varieties of this figure of contrast. The analysis is applied in the linguistic examination of the Sonnets written by William Shakespeare. When studying, systemizing and analyzing the opposite units, it is extremely important to study their structural features. The main objective of this study is to identify and describe the types of oxymoron in the language of Shakespeare’s sonnets.